Luminous and Obscured Quasars and Their Host Galaxies - Del Moro, Agnese; Alexander, David M.; Bauer, Franz E.; Daddi, Emanuele; Kocevski, Dale D.; Stanley, Flora; McIntosh, Daniel H. (Frontiers in Astronomy and Space Sciences, 2018)
The most heavily-obscured, luminous quasars might represent a specific phase of the evolution of the actively accreting supermassive black holes and their host galaxies, possibly related to mergers. We investigated a sample of the most luminous quasars at z ≈ 1 − 3 in the GOODS fields, selected in the mid-infrared band through detailed spectral energy distribution (SED) decomposition. The vast majority of these quasars (∼80%) are obscured in the X-ray band and ∼30% of them to such an extent, that they are undetected in some of the deepest (2 and 4 Ms) Chandra X-ray data. Although no clear relation is found between the star-formation rate of the host galaxies and the X-ray obscuration, we find a higher incidence of heavily-obscured quasars in disturbed/merging galaxies compared to the unobscured ones, thus possibly representing an earlier stage of evolution, after which the system is relaxing and becoming unobscured.